Epigenetic regulation of bud dormancy events in perennial plants - Ríos, Gabino; Leida, Carmen; Conejero, Ana; Badenes, María Luisa (Frontiers in Plant Science, 2014)
Release of bud dormancy in perennial plants resembles vernalization in Arabidopsis thaliana and cereals. In both cases a certain period of chilling is required for accomplishing the reproductive phase, and several transcription factors with the MADS-box domain perform a central regulatory role in these processes. The expression of DORMANCY ASSOCIATED MADS-box (DAM)-related genes has been found to be up-regulated in dormant buds of numerous plant species such as poplar, raspberry, leafy spurge, blackcurrant, Japanese apricot and peach. Moreover, functional evidence suggests the involvement of DAM genes in the regulation of seasonal dormancy in peach. Recent findings highlight the presence of genome-wide epigenetic modifications related to dormancy events, and more specifically the epigenetic regulation of DAM-related genes in a similar way to FLOWERING LOCUS C (FLC), a key integrator of vernalization effectors on flowering initiation in Arabidopsis. We revise the most relevant molecular and genomic contributions in the field of bud dormancy, and discuss the increasing evidence for chromatin modifications involvement in the epigenetic regulation of seasonal dormancy cycles in perennial plants.